Technology as a Social Learning and Citizen Facilitator - da Silva, D; Belchior-Rocha, H. (Swarm Intelligence Applications for the Cities of the Future, 2025)
The chapter delves into the complex relationship between social learning and citizen engagement within the context of future cities. It highlights the significance of technology in shaping the evolution of urban spaces and emphasizes the pivotal role it plays in fostering community participation and active involvement. Drawing on historical events such as the SARS-CoV-2 pandemic and the 9/11 attacks, the chapter underscores the importance of citizen learning and exchange of information in responding to challenges and shaping societal resilience. Before the discussions on social learning theory and citizen engagement, the chapter provides a foundational understanding of these concepts and their interplay. It elucidates how advancements in technology, from Artificial Intelligence to interactive communication interfaces, are instrumental in enhancing citizen participation and promoting social cohesion within future city environments. By leveraging technologies such as virtual reality tours and AI-powered interaction, cities can facilitate informed decision-making and foster a sense of community ownership in urban development initiatives. Furthermore, the chapter emphasizes the growing role of AI in citizen engagement, noting its potential to catalyze collaborative intelligence and enable more transparent decision-making processes. It advocates for the integration of innovative technologies to empower residents and enhance the inclusivity of policy-making endeavors. Ultimately, the chapter underscores the transformative potential of leveraging social learning and citizen engagement in shaping the future landscape of smart cities, underscoring the pivotal role of community voices in driving sustainable urban development.